1991
DOI: 10.1002/jlb.50.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Interferon Production by Human Monocytes: Requirements for Priming for Lipopolysaccharide-Induced Production

Abstract: Macrophages are uniquely responsive to bacterial lipopolysaccharide (LPS) for activation of a number of host defense functions and production of bioactive mediators. One potentially important mediator produced by LPS-stimulated macrophages is interferon (IFN-alpha/beta). In contrast to murine observations, we have observed that freshly isolated human monocytes, purified by counter-current centrifugal elutriation, do not produce interferon in response to LPS. This is not due to a lack of response to LPS, as ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 16 publications
3
37
0
Order By: Relevance
“…Priming of cells for faster and stronger activation of defense upon a stress stimulus plays an important role in various forms of IR in plants and animals (Hayes et al, 1991;Conrath et al, 2006;Pham et al, 2007). Until now, the identity of hypothetical signaling components that would accumulate during priming but be employed only upon exposure to challenge stress has been obscure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Priming of cells for faster and stronger activation of defense upon a stress stimulus plays an important role in various forms of IR in plants and animals (Hayes et al, 1991;Conrath et al, 2006;Pham et al, 2007). Until now, the identity of hypothetical signaling components that would accumulate during priming but be employed only upon exposure to challenge stress has been obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Although priming has been known as a component of IR responses in plants (Kuć , 1987;Zimmerli et al, 2000;Verhagen et al, 2004) and mammals (Hayes et al, 1991) for several years, and recently has been associated with an adaptive immune response in Drosophila melanogaster as well (Pham et al, 2007), very little is known about the molecular mechanism(s) of priming. It has been proposed that priming is associated with increased accumulation of inactive cellular signaling proteins that play an important role in signal amplification (Conrath et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Monocytic cells are among the main producers of type I IFNs following viral challenge or stimulation with bacterial endotoxin. Although secretion of IFN-␤ was observed in murine peritoneal macrophages treated with IFN-␥ (46), it was shown that freshly isolated human monocytes did not produce type I IFNs in response to single IFN-␥ or LPS stimulation, but needed to be primed by either IFN-␥ or GM-CSF (47). In agreement with these results, we have demonstrated by quantitative RT-PCR analysis that human monocytes and dendritic cells have a very low or undetectable level of IFN-␤ mRNA that is not inducible by IFN-␥ treatment alone.…”
Section: Discussionmentioning
confidence: 99%
“…This mode of protection confers enhanced resistance without direct activation of defense mechanisms upon induction treatment. By analogy with a phenotypically similar phenomenon in animals and humans (Hayes et al, 1991;Wyatt et al, 1996), this enhanced capacity to express basal defense mechanisms is called sensitization, potentiation, or priming .…”
Section: Introductionmentioning
confidence: 99%